Determinan terhadap Kepatuhan Penggunaan Alat Pelindung Diri (APD) : Determinants of Compliance with the Use of Personal Protective Equipment (PPE) - Iskandar, Muhammad Wahid (MPI Press, 2022)
Background: Approximately 321,000 cases are due to work accidents and about 2.02 million are due to work-related diseases. In Indonesia, there is an average of 99,000 cases of work accidents per year. Out of this total, about 70 percent result in fatal consequences such as death and lifelong disabilities. In Indonesia, the number of work accidents is quite concerning. According to data from BPJS Ketenagakerjaan, in 2018, there were 114,148 workplace accidents, while in 2019, there were 77,295 cases. However, it increased to 153,044 cases in 2020. Objective: To determine the relationship between attitude, occupational health and safety (K3) policies, and supervision on compliance with the use of personal protective equipment (PPE) at PT. SKF Indonesia in 2021. Method: This research is a quantitative cross-sectional study. The study population consists of all production workers involved in bearing production at PT SKF in 2021, totaling 196 people. The researchers used purposive sampling techniques, resulting in a sample size of 131 people. The research instrument for data collection was a questionnaire to gather respondent information. Bivariate data analysis was performed using the Chi-Square test. Results: Based on the Chi-Square statistical test, the research results indicate that the attitude (p-value = 0.000 ≤ 0.05); OR (95% CI = 5.413), K3 policies (p-value = 0.000 ≤ 0.05); OR (95% CI = 4.237), and supervision (p-value = 0.000 ≤ 0.05); OR (95% CI = 4.843) all show significant relationships. Conclusion: There is a significant relationship between attitude, K3 policies, and supervision with compliance in the use of PPE among construction workers at PT. SKF Indonesia in 2021.